PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA YOUTUBE TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS VII SMP NEGERI 35 MEDAN - Nia Damai Putri Br Sitorus; Prihasti Wuriyani, Elly (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the ability of seventh-grade students at SMP Negeri 35 Medan in writing news texts using the Project Based Learning model, to determine the ability of students in writing news texts using the direct instruction model, and to determine the effect of the Project Based Learning model on students’ ability in writing news texts. The research method used in this study was a quasi experimental method. The population of this study consisted of all seventh-grade students of SMP Negeri 35 Medan. The sample consisted of two classes, namely the experimental class with 32 students and the control class with 31 students. Data were collected through a news text writing test. The data were analyzed using normality test, homogeneity test, and hypothesis testing with the t-test. The results showed that the students’ ability in writing news texts using the Project Based Learning model obtained an average score of 81.41 and was categorized as very good. Meanwhile, the students’ ability in writing news texts using the direct instruction model obtained an average score of 70.45 and was categorized as sufficient. Based on the hypothesis testing, it was found that t_count > t_table, namely 3.04 > 2.00 at the significance level α = 0.05 with degrees of freedom (df) = 61. Therefore, the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Based on the results of this study, it can be concluded that the Project Based Learning model has a significant effect on the ability of seventh-grade students at SMP Negeri 35 Medan in writing news texts.